An analogue memristor made of silk fibroin polymer. Issue 41 (15th October 2021) - Wang, Wenhua; Zhou, Guangdong; Wang, Yuchen; Sun, Bai; Zhou, Mengyuan; Fang, Changxiang; Xu, Cunyun; Dong, Jun; Wang, Feng; Duan, Shukai; Song, Qunliang
Abstract : A novel protein-based polymer memristor is synthesized by a polymerization reaction using silk fibroin protein (SFP) and 2-isocyanatoethyl methacrylate. Abstract : A novel protein-based polymer memristor is synthesized by a polymerization reaction using silk fibroin protein (SFP) and 2-isocyanatoethyl methacrylate. The analogue-type protein-based memristor demonstrates that more than 32 conductance levels are impressively obtained and outstandingly maintained for 4 months. This work provides a new horizon for high performance analogue computing systems.